Pengaruh Metode Hypnoteaching Terhadap Minat dan Hasil Belajar Siswa pada Pokok Bahasan Statistika di SMP Muhammadiyah 16 Surabaya - Fara Diba Nur Cholifatun Nissa’; Sutopo Sutopo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research is motivated by the low interest and student learning outcomes. Therefore, researchers assume that the use of a new learning model is expected to be able to increase student interest in teaching and learning activities and be able to improve student learning outcomes. In this case the researcher wanted to know how far the influence of the hypnoteaching method had on the interest and learning outcomes of class VIII students on the subject of statistics at Muhammadiyah 16 Junior High School Surabaya. The research approach used is quantitative. This type of research is a quasi experiment. The population in this study were students of class VIII SMP Muhammadiyah 16 Surabaya. The sampling technique used is saturated sampling. Data collection techniques using questionnaires, tests, and documentation. The data analysis technique used was the t test and the Manova test. The results showed that there is an influence of the application of the hypnoteaching method on the interest and learning outcomes of class VIII students on the subject of statistics at Muhammadiyah 16 Junior High School Surabaya.